The digitization of higher education with a socioformative approach: A documentary analysis - Valles Baca, Herik Germán; Parra Acosta, Haydee (IE Revista de Investigación Educativa de la REDIECH, 2021)
Education, faced with uncertain scenarios due to the current pandemic, has had to adapt, giving rise to the new higher education. The purpose of this paper is to show a documentary analysis of the challenges of the digitalization of higher education in the current times. Conceptual mapping was used as a methodological strategy for the organization of information, following the eight axes. To meet the objectives of the mapping, it was necessary to search for information from various sources, where different university models corresponding to this new higher education were reviewed, including the UACH-DS Educational Model of the Universidad Autónoma de Chihuahua, Mexico. The results showed that recent higher education models go beyond favoring academic learning in students, they seek to train them as integral human beings in multiple fields, applying technological tools with a socio-formative approach according to the current context and the knowledge society. The main conclusion was that Information and Communication Technologies (ICT) and Learning and Knowledge Technologies (LKT), from a socio-formative approach, promote integral and humanistic formation from a new perspective of the educational process.